Research on illustration techniques of Japanese comic - Tiong, Hui Ming, (Universiti Malaysia Sarawak (UNIMAS), 2005)
This is a research on illustration techniques of Japanese comics. I am investigating the types of illustrations techniques that are preferable by most comics readers. From the questionnaire and interview analysis, majority of the people prefferred comic drawn by pen and ink and computer graphic effects. Therefore, e-comic and its promotions based on pen and ink with computer graphoc modification are introduced. As a conclusion, the illustrations techniques used has produced a good result of e-comic and it promotional mediums. This is due to combination of two illustration techniques can overcome the limitations posed by single illustration technique. Thus, using combination of two illustration techniques (pen and ink and computer graphic) can produce a more satisfactory result compare to using single illustration technique alone.